Friends hold all things in common : tradition, intellectual property, and the Adages of Erasmus - Eden, Kathy, 1952- (Yale University Press, 2001)
This study of Erasmus's Adages focuses on both the commitment to friendship & common property that Erasmus shares with his favourite philosophers & the early history of private property that transforms European attitudes concerning the right to copy.